Historical biogeography of neotropical freshwater fishes - Albert, James S.; Reis, Roberto E. (University of California Press, 2011)
The fish faunas of continental South and Central America constitute one of the greatest concentrations of aquatic diversity on Earth, consisting of about ten percent of all living vertebrate species. This title explores the evolutionary origins of this unique ecosystem.